Exploring issues and challenges in education among youth in Selangor - Che Nawi, Nur Raihan; Arshad, Mohd Mursyid; Othman, Mohd Khariruddin; Ismail, Ismi Arif; Abdullah, Haslinda; Krauss, Steven Eric; Abd Aziz, Mohd Faiq; D’Silva, Jeffrey Lawrence; Dahalan, Dzuhailmi; Mohammed Shaffril, Hayrol Azril; Hamzah, Siti Rabaah; Ridzwan Jamaluddin, Mohammad Syafiq; et al. (Human Resources Management Academic Research Society (HRMARS), 2024)
Education has always been regarded as the cornerstone of any society's growth and prosperity. It's the pathway to dreams realized and ambitions achieved. However, for an alarming number of young minds in Selangor, this pathway is strewn with obstacles, making their journey to knowledge and enlightenment an arduous one. Therefore, this study will explore the educational issues faced among youth in Selangor. This study employs a qualitative research method through interviews (with informants selected via purposive sampling techniques. The criteria for informants are essential in this study to ensure they represent the voices of youth in Selangor. The method of focused group discussions (FGD) using open-ended and unstructured questions was conducted to gather feedback from informants, particularly regarding the issues faced in education among youth in Selangor. The focused group discussion sessions have aided the researchers in gaining insights into the views and aspirations of the youth in Selangor within the domain of education. In these discussions, three (3) main themes. The findings also indicate a lack of guidance for youth regarding their paths after the Sijil Pelajaran Malaysia (SPM). Therefore, the state needs to disseminate information about education initiatives to youth using more youth friendly mediums.